MORPHOLOGICAL CHANGES IN THE LIVER IN EXPERIMENTAL DIABETES (Eureka Journal of Physical and Chemical Research, 2025)
Diabetes is one of the intensively developing diseases, and chronic hyperglycemia causes protein glycosylation, glucose autoxidation, and a sharp increase in the active forms of oxygen. Chronic hyperglycemia causes high oxidative stress. As a result, the amount of free radicals increases. This causes damage to the heart, kidney, blood vessels and nervous system of vital organs [15].